Analysis of innovative activity in agricultural organizations in the field of general farming and crop production for the period 2003–2022 taking into account the peculiarities of the dynamics of the results of intellectual activity - Е. V. Leun; S. E. Pchelkin; A. Yu. Romanov (Омский научный вестник: Серия "Общество. История. Современность")
The article discusses three groups of Results of Intellectual Activity of agribusiness organizations on the topic of general agriculture and crop production for the period 2003–2022. The first two groups of Results of Intellectual Activity include patents from Russia, the USA, the European Union and China. Of these, the first group combines patents in accordance with the classes of the International Patent Classification: A01B, A01C and A01D. The second group covers high-tech patents selected for these three classes of the International Patent Classification with the addition of the fourth: G — physics. In the third group of Results of Intellectual Activity, Russian patents from the first group of Results of Intellectual Activity and Russian dissertations defended in scientific specialties 06.01.01 «General farming, crop production» and 4.1.1 «General farming and crop production» before and after changes in their nomenclature in 2021, respectively, are collected and studied. The parameters that characterize these groups of Results of Intellectual Activity are proposed, the features of the influence of the dynamics of their patent and scientific activity on innovation activity are studied.